Creating digital knowledge: Library as open access digital publisher. Issue 2 (2nd October 2017) - Bailey, D. Russell
ABSTRACT: Since the mid-1990s, many higher education libraries have evolved from the traditional roles of primarily (1) research resource purchasers and providers and (2) research service providers into new, enhanced, and complementary digital age roles related to digital open access knowledge creation and digital publishing, creating digital resources for open education. This article presents a brief description of open access digital knowledge creation, the library publishing landscape (particularly in Digital Humanities/DH), as well as several model higher education library approaches and example initiatives in these areas. These models and initiatives are presented as broadly adaptable and scalable to many higher education libraries throughout the world, even where variations in change-readiness; size; and fiscal, staff, and technology resources exist. The real-world examples presented here focus on three specific humanities disciplines: U.S. history, art and art history, and Latin American literature and art. These examples invite readers to consider how such open access knowledge creation and digital publishing are both feasible and useful in their higher education libraries.